Hemodialysis and Water Quality. Issue 4 (17th July 2013) - Coulliette, Angela D.; Arduino, Matthew J.
Abstract Over 383, 900 individuals in the U.S. undergo maintenance hemodialysis that exposes them to water, primarily in the form of dialysate. The quality of water and associated dialysis solutions have been implicated in adverse patient outcomes and is therefore critical. The Association for the Advancement of Medical Instrumentation has published both standards and recommended practices that address both water and the dialyzing solutions. Some of these recommendations have been adopted into Federal Regulations by the Centers for Medicare and Medicaid Services as part of the Conditions for Coverage, which includes limits on specific contaminants within water used for dialysis, dialysate, and substitution fluids. Chemical, bacterial, and endotoxin contaminants are health threats to dialysis patients, as shown by the continued episodic nature of outbreaks since the 1960s causing at least 592 cases and 16 deaths in the U.S. The importance of the dialysis water distribution system, current standards and recommendations, acceptable monitoring methods, a review of chemical, bacterial, and endotoxin outbreaks, and infection control programs are discussed.